Effect of morphological type of extrauterine ectopic pregnancy on accuracy of preoperative ultrasound diagnosis. (6th September 2019) - Dooley, W. M.; Chaggar, P.; De Braud, L. V.; Bottomley, C.; Jauniaux, E.; Jurkovic, D.
ABSTRACT: Objectives: To assess the overall accuracy of transvaginal ultrasound (TVS) for diagnosis of all types of extrauterine ectopic pregnancy (EUEP) in a large group of women who were managed surgically. We also aimed to assess the positive predictive value (PPV) of TVS for each of the different ultrasound morphological types of EUEP. Methods: This was a retrospective observational study of all pregnant women who underwent emergency surgery following ultrasound diagnosis of EUEP at a single early pregnancy unit between January 2009 and December 2017. The preoperative TVS findings were recorded, including the exact location and morphological type (Type I–V; defined using ultrasound criteria) of EUEP. TVS findings were compared with operative and histological findings. The performance of ultrasound in diagnosing EUEP overall and according to morphological type was assessed, using visual confirmation of ectopic pregnancy at surgery as the reference standard. Results: A total of 26 401 women presented with early‐pregnancy complications during the study period, including 1241 (4.7%; 95% CI, 4.5–5.0%) women with a conclusive diagnosis of EUEP on TVS or a presumed diagnosis based on severe pain and significant hemoperitoneum. Surgery was performed in 721/1241 (58.1%; 95% CI, 55.3–60.8%) cases, of which 710 (98.5%; 95% CI, 97.6–99.4%) had a conclusive diagnosis of EUEP on preoperative TVS. The remaining 11 women had severe pain and significant hemoperitoneum and were managed surgically on clinical grounds as an emergency, without an ectopic pregnancy having been identified on ultrasound examination. At laparoscopy, the diagnosis of EUEP was confirmed in 706/710 (99.4%; 95% CI, 98.6–99.8%) women with a positive ultrasound diagnosis and in all 11 women with a presumed ultrasound diagnosis of EUEP. The PPV of preoperative ultrasound for the diagnosis of EUEP was 99.4% (95% CI, 98.6–99.8%) with sensitivity of 98.5% (95% CI, 97.3–99.1%). There was no statistically significant difference in the accuracy of preoperative ultrasound diagnosis between the five morphological types ( P  = 0.76). Conclusions: The accuracy of preoperative ultrasound for diagnosis of EUEP is high. The morphological type of EUEP on TVS had no significant effect on the accuracy of preoperative diagnosis. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.